Classification of fixed assets for accounting purposes in the public sphere - T. L. Leukhina (Вестник университета)
The article reveals the concept of fixed assets, which is used in the accounting system of the public sector. The points of view of scientists on the problem of accounting (budgetary) accounting of fixed assets are considered, their work is analyzed in terms of the completeness of disclosure of types of long-term assets. New classification features are proposed, the types of fixed assets are specified from the standpoint of the current accounting and budgetary legislation.The types of fixed assets that characterize the availability and condition, including those as of the inventory date, having a cost characteristic, signs of impairment, depending on the depreciation group and depreciation method, are determined. The interrelation of the introduced types of fixed assets with economic benefits and useful potential is indicated. The types of fixed assets from the standpoint of public procurement are identified. Explanations of the introduced groupings are given.